ESI(+)-MS and GC-MS Study of the Hydrolysis of N-Azobenzyl Derivatives of Chitosan - Pereira, Fernanda S. [UNESP]; Nascimento, Heliara D. L.; Magalhaes, Alvicler; Peter, Martin G.; Bataglion, Giovana Anceski; Eberlin, Marcos N.; Gonzalez, Eduardo R. P. [UNESP] (Mdpi Ag, 2014)
New N-p-chloro-, N-p-bromo-, and N-p-nitrophenylazobenzylchitosan derivatives, as well as the corresponding azophenyl and azophenyl-p-sulfonic acids, were synthesized by coupling N-benzylvchitosan with aryl diazonium salts. The synthesized molecules were analyzed by UV-Vis, FT-IR, H-1-NMR and N-15-NMR spectroscopy. The capacity of copper chelation by these materials was studied by AAS. Chitosan and the derivatives were subjected to hydrolysis and the products were analyzed by ESI(+)-MS and GC-MS, confirming the formation of N-benzyl chitosan. Furthermore, the MS results indicate that a nucleophilic aromatic substitution (SnAr) reaction occurs under hydrolysis conditions, yielding chloroaniline from N-p-bromo-, and N-p-nitrophenylazo-benzylchitosan as well as bromoaniline from N-p-chloro-, and N-p-nitrophenylazobenzyl-chitosan.
Keywords: chitosan; N-azobenzylchitosan; ESI-MS; GC-MS; SnAr reaction